Argon mediates protection by interleukin‐8 suppression via a TLR2/TLR4/STAT3/NF‐κB pathway in a model of apoptosis in neuroblastoma cells in vitro and following ischemia‐reperfusion injury in rat retina in vivo. Issue 6 (30th May 2016) - Ulbrich, Felix; Lerach, Teresa; Biermann, Julia; Kaufmann, Kai B.; Lagreze, Wolf A.; Buerkle, Hartmut; Loop, Torsten; Goebel, Ulrich
Abstract: Argon has recently come into scientific focus as a neuroprotective agent. The underlying neuroprotective mechanism remains unknown although toll‐like receptors were recently suggested to play an important role. We hypothesized that TLR‐associated downstream transcription factors are responsible for argon's effects, leading to anti‐apoptotic and anti‐inflammatory properties. Apoptosis was induced in human neuroblastoma cells. Immediately afterwards, argon treatment (75 Vol% for 2 h) was initiated. Cells were analyzed, measuring mitochondrial membrane potential, reactive‐oxygen‐species, annexin‐V/propidium iodide staining, transcription factor phosphorylation and binding activity as well as protein and mRNA expression of interleukins. Argon's in vivo effects were analyzed by quantification of retinal ganglion cell density, mRNA expression, serum cytokine analysis and immunohistochemistry after retinal ischemia reperfusion injury (IRI) in rats. Argon diminished rotenone‐induced kappa‐light‐chain‐enhancer' of activated B‐cells (NF‐κB) and signal transducer and activator of transcription 3 (STAT3) but not STAT5 or cAMP‐response element‐binding protein (CREB) phosphorylation and DNA‐binding activity. Argon treatment attenuated apoptosis by preservation of mitochondrial membrane potential and decline in reactive oxygen species (ROS) generation. NF‐κB and STAT3 inhibition, as well as TLR2 and TLR4 inhibition reversed argon's effects on IL‐8 mRNA expression. Argon attenuated rotenone‐induced IL‐8 protein and mRNA expression in vitro . Inhibition of TLR2 and 4 attenuated argon's protective effect in vivo reducing IRI driven retinal IL‐8 expression. IL‐8 expression was found in the retina in co‐localization with Müller cells and retinal ganglion cells. Argon mediates its neuroprotective effects by TLR‐mediated regulation of transcription factors NF‐κB and STAT3, thus decreasing interleukin‐8 expression in vitro and in vivo . These findings may open up new opportunities to effectively treat cerebral ischemia and reperfusion injury through the inhalation of argon. Argon exerts its protective effects in vitro and in vivo via toll‐like receptors TLR2 and TLR4 signaling, followed by alteration of downstream enzymes. In conclusion, argon mediates its beneficial effects by suppression of STAT3 and NF‐κB phosphorylation and subsequent suppression of interleukin IL‐8 protein expression. These novel findings may open up opportunities for argon as a therapeutic agent, particularly in the treatment of neuronal injury. Cover image for this issue: doi:10.1111/jnc.13334 . Abstract : Argon exerts its protective effects in vitro and in vivo via toll‐like receptors TLR2 and TLR4 signaling, followed by alteration of downstream enzymes. In conclusion, argon mediates its beneficial effects by suppression of STAT3 and NF‐κB phosphorylation and subsequent suppression of interleukin IL‐8 protein expression. These novel findings may open up opportunities for argon as a therapeutic agent, particularly in the treatment of neuronal injury. Cover image for this issue: doi:10.1111/jnc.13334 .